Long‐chain PUFA enrichment in microalgae and metabolic dynamics in Tapes philippinarum larvae. (4th February 2015) - Ventrella, V.; Gatta, P. P.; Zentilin, A.; Pagliarani, A.; Trombetti, F.; Bonaldo, A.; Nesci, S.; Pirini, M.
Abstract: The possibility of increasing n‐3 and n‐6 long‐chain polyunsaturated fatty acids (PUFA) content in microalgal mixtures used to feed Tapes philippinarum larvae was explored by lowering culture temperature from 26 to 14 °C. Although fatty acid composition of different microalgal species has a genetic basis, the algal cultures grown at 14 °C significantly increased the content of long‐chain n‐3 PUFA in Isocrysis galbana and in Thalassiosira pseudonana, while in Tetraselmis tetrathelo, the PUFA increase only involved shorter chain PUFA, namely 16:4n‐3 and 18:4n‐3. However, larvae fed on the PUFA enriched microalgal mixture did not show improvements in growth and survival performances with respect to the control group fed the microalgal mixture grown at 26 °C. From a biochemical perspective, two key aspects emerged from the results: (i) clam larvae have adequate biotransformation and selection skills to adjust fatty acid profile to their requirements as they can even modulate the incorporation of essential long‐chain PUFA as 20:5n‐3 and 22:6n‐3 when the dietary supply exceeds the physiological requirements; (ii) bivalve can biosynthesize non‐methylene‐interrupted dienoic (NMID) fatty acids as confirmed by the constancy of relative proportion with larvae growth in spite of the NMID fatty acid absence in the diet.